Pengembangan Model Latihan Passing Bawah melalui Permainan Kecil pada Siswa Ekstrakurikuler Bola Voli di SMA Negeri 2 Tungkal Jaya - Andy Rifaldo; Siti Ayu Risma Putri; Husni Fahritsani (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study aims to improve the quality of lower passing in volleyball extracurricular students at SMA Negeri 2 Tungkal Jaya by developing a model of lower passing training through small games in the final product of the book. This type of research is research and development (Reseach & Development) using the ADDIE model, this model consists of five stages including: 1) analyze, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. This research produces products that are validated by material experts, and media experts. The resulting product was tested on students who participated in volleyball extracurricular activities at SMA Negeri 2 Tungkal Jaya through small-scale trials and large-scale trials using Questionnaire Data. The data obtained from the Small Group Trial got a percentage of 90.16% and the data obtained from the Large Group Trial got a percentage of 88.94%.